Tecendo uma rede de sociabilidades: visibilidade ao fundo documental Guilhermino César da Silva no IHGRGS - Feijó, Thais Nunes (2015)
This dissertation is the result of research on the Documentary Fund Guilhermino César da Silva belonging to the Historical and Geographical Institute of Rio Grande do Sul. Attention was paid to the importance of intellectual living in RS in 1943, coming from Minas Gerais as Chief of Staff of Ernesto Dornelles Federal Interventor in Rio Grande do Sul. Guilhermino Caesar graduated in law and in addition to holding office as Chief of Police Head Office in Belo Horizonte, Secretary of Rio Grande do Sul State Finance and the Minister of Court State Audit of Rio Grande do Sul, was also a writer, columnist and university professor. The Documentary Fund Guilhermino César da Silva researched here, consists of documents and objects that depict his family life, correspondence exchanged with friends, professional and student life are also contemplated in the Fund allows us to know that a significant part of his public life and private and your network of contacts. We emphasize the importance of it to constitute the memory of intellectual, to the memory of the RS and as equity or of the cultural state of Rio Grande do Sul. Our goal is to give greater visibility to the Documentary Fund Guilhermino César da Silva guarded by the Historical and Geographical Institute of Rio Grande do Sul, which is expected to achieve by adopting the cultural project, elaborated in the annex to this research.